Šibenska katedrala u djelima austrijskih pisaca - korijeni jednog "slučaja" - Marković, Predrag (Array, 2004)
St. jacob's cathedrl in šibenik is among the rare postmedieval monuments whose rich, 150 years ols history of studying ofers us an exceptional view to the development of historiography of arthistory on Croatian soil, from Ivan Kukuljević Sakcinski to our time. After a short review of the most significant viewpoints and opinions from second half of the 19th century, especialy of a German speaking authors (R, Eitelberger von Edelberger, J. Graus), the paper deals with two basic , and until now most complete studies on the Šibenik cathedral - a monograph by Dagobert Frey (Der Dom von Sebenico und Seine Baumaister Giorgio Orsini, 19139 , and a developmentaly syntethic treatise by Hans Folnescis (Studien zur Entwicklungsgeschihte der Architectur und Plastik des XV. Jahrhhunderts in Dalmatien, 1914. This two Austrian writers presented almost contradictory opinions aobut basic problems of the orgin, authorshio and stylistic determination on Šibenik cathedral and their works for the first time they clearly formed two important "schools" of research on Šibenik Cathedral - firstly the "Renaissance" or "Georgian" one advocated by D. Frey, and secondly , the "developmental" one, exposed by H. Folnescis. Therefore, we briefly reveiew proponents of both "schools" , and partly point to ideeological and other circumstances that determined the reception of their work in the folowing period. From this angle, a special attention is given to works by two Italian autors between the wars: Alessandro Dudan and Attilio Tamaro ; in their voluminous, irredentisticaly concieved reviews of Dalmatian arts, they secured an important place for Šibenik cahtedral and its architect, Juraj Matijev Dalmatinac. Finally, we present views and attitudes of Aldolfo Venturi, wich had a considerable influence on most of the researches who studiede the orgin of Šibenik cathedral.